An examination of Chinese students'decision making behavior on the choice of UK University for a master’s degree - Liang, Junqing (2013)
The purpose of this dissertation is to examine the factors which can influence Chinese students’ intention to study in the UK for a master’s degree. Variables to be investigated include attitudes, subjective norms, internal control, external control, and intention. In addition, the effects of past experience were also examined.